DEVELOPMENT OF COMMUNITY BASED REHABILITATION MODELS FOR CHILDREN IN CONFLICT WITH THE LAW: AN IMPLEMENTATION STUDY AT THE CLASS II JUVENILE DETENTION CENTER IN JAYAPURA - Damayana, Sri Nur; Mufty, Abdul Malik (fakultas hukum universitas PGRI Semarang, 2025)
Children in Conflict with the Law (CICL) require handling based on restorative and rehabilitative justice to support social reintegration, as mandated by the Juvenile Justice Act. However, the Class II Juvenile Detention Center (LPKA) in Jayapura faces challenges such as limited facilities, budget constraints, family participation, and geographic accessibility. This study aims: (1) to analyze the actual conditions of CICL rehabilitation at the Class II LPKA Jayapura; (2) to identify principles of modern penology and restorative justice for a community-based rehabilitation model; and (3) to develop a rehabilitation model appropriate to the Papuan context. The research employed an empirical juridical method with case and conceptual approaches, collecting primary data through interviews and secondary data from literature studies. The results indicate that multidimensional constraints remain dominant, although innovative programs like